Regulation and performance of communication and information networks - Faulhaber, Gerald R.; Madden, Gary.; Petchey, Jeff. (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2012)
"Digital markets worldwide are in rapid flux. The Internet and World Wide Web have traditionally evolved in a largely deregulated environment, but recently governments have shown great interest in this rapidly developing sector and are imposing regulations for a variety of reasons that are changing the shape of these industries. This book explores why the industrial organization of broadband ISPs, Internet backbone providers and content/application providers are in such turmoil. The expert contributors straddle the turbulent past of the telecoms sector and also contribute to its exciting--though unpredictable--future via positive analysis of past communications policies, which is then utilized to deduce lessons to guide future policy making decisions. It is illustrated that broadband ISPs no longer simply provide a conduit for service delivery; they are also involved in producing content and transaction services themselves, in competition with content and delivery providers. The blurring of the traditional lines between these three sectors, as each enters into the others' markets, is highlighted. The conclusion is that we are witnessing the emergence of powerful, competing platforms, linked in complex ways that challenge traditional economic analyses. Exploring governance issues, regulation and investment, next-generation service markets and wireless communication, this book will prove a fascinating and illuminating read for scholars, researchers, post-graduate students and policymakers with an interest in ICT, technology and innovation, economics and industrial organization"--Provided by publisher.
Challenges of institutional governance for network infrastructures : reinstitution and expansion of legal innovations / Barbara A. Cherry -- Beyond traditional regulatory models : emerging governance for new networks / Rob Albon -- Government oversight of next generation wireless networks / Rob Frieden -- Incentive regulation, investments and technological change / Ingo Vogelsang -- Policy and regulation for next generation networks / Martin Cave -- Sector regulation and investment incentives : the European experience / Harald Gruber -- Pricing of complements and network effects / Nicholas Economides and Brian Viard -- Spillovers and network neutrality / Christiaan Hogendorn -- Network neutrality and sector performance : exploring policy options with simulation methods / Kurt DeMaagd and Johannes M. Bauer -- Mobile communications : economic and social impact / Gerald R. Faulhaber -- Regulator incentives and third generation national mobile telecommunications market entry / Gary Madden, Aaron Morey, and Erik Bohlin -- Licensing options for digital dividend spectrum : an Australian perspective / Benoît P. Freyens -- Two-sided markets with substitution : mobile termination revisited / Jerry A. Hausman -- Policy implications of asymmetric termination rate regulation in Europe / Edmond Baranes and Cuong Huong Vuong -- The absence of data for measuring the economic impact of IT in the US / Shane Greenstein.
Includes bibliographical references and index.
Keywords: Computer networks -- Law and legislation